PERAN KETELADANAN GURU PENDIDIKAN AGAMA KATOLIK DALAM UPAYA MEMBUDAYAKAN SIKAP TOLERANSI BERAGAMA DALAM DIRI PESERTA DIDIK DI SMPK PHALADHYA WAIWERANG - Anna Maria Rosita Kw; Alfonsus Mudi Aran (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesia is a country with diverse ethnicities, races, cultures, and religions. The diversity of the Indonesian nation is often misunderstood as a difference by Indonesian society. Therefore, the last few years have witnessed various conflicts, one of which is related to religious intolerance among students that occurs in schools. Therefore, the active role of educators is very necessary to resolve these conflicts. The purpose of this study was to determine the role of Catholic Religious Education teachers' role models in cultivating an attitude of religious tolerance among students at SMPK Phaladhya. The research method used was descriptive qualitative. Qualitative descriptive research can help gain a deeper understanding of the phenomenon studied and contribute to the development of more accurate theories. The findings indicate that the role of Catholic Religious Education teachers' role models in cultivating an attitude of religious tolerance among students at SMPK Phaladhya is very good. However, it was found that some students did not understand and comprehend the importance of living a tolerant life, resulting in frequent conflicts of religious intolerance between students. This study was conducted because of the occurrence of these conflicts of intolerance. The novelty in this research is that this research is more specific to PAK teachers as role models in the context of junior high Catholic schools, where the challenges of religious learning have different characteristics from other religion-based schools and this research integrates the role model of a Catholic Religious Education teacher in cultivating an attitude of religious tolerance in students.